A new morphological approach to Iranian bazaar: the application of urban spatial design theories to Shiraz and Kerman bazaars. Issue 3 (2nd September 2018) - Lak, Azadeh; Hakimian, Pantea
ABSTRACT: Situated at the center of cities, Iranian bazaars have not only shaped the structure of cities but also serve as a fundamental urban space. In recent decades, unsustainable developments deteriorating the old historic districts of cities have negatively influenced the physical, economic, and social aspects of bazaars. This is the most serious challenge of urban regeneration. Focusing on Shiraz and Kerman bazaars, the present research aims at proposing a new approach for studying the morphology of Iranian bazaars as highly distinguished urban sites. The qualitative method was applied to analyze these cases by conducting desk and field studies while investigating the historical maps of Shiraz and Kerman bazaars according to Trancik's theories of urban spatial design (1986. Finding lost space: theories of urban design . John Wiley & Sons). Then, content analysis was used to extract the associated meaning of bazaar through in-depth interviews. The results show that Iranian bazaars, as an important urban space, have a pivotal organizational pattern according to figure-ground theory. Moreover, the so-called linkage theory suggested a group form and mega form role for Iranian bazaars which shapes the most important structure of the connections. Finally, the results of place theory indicated that these bazaars carry a symbolic value for nearby residents.